Sistem Informasi Eksekutif Berbasis Web Pada Stasiun Pengisian Bahan Bakar Umum (SPBU) PT. PERTAMINA - Ostarisa, Edo; Wibowo, Januar; Taufik, Vicky M (Jurnal JSIKA, 2012)
Fuel Retail Marketing Regional V is one of the functions contained in the PT. Pertamina UPMS V Surabaya where the his job to handle the retail marketing of fuel through a dealer institutions like Gas Station. Gas Station itself is deemed necessary to make corrections and special attention, because the Gas Station is the tip of the marketing of fuel directly into contact with end customers. So it is not uncommon Pertamina executives require information that is useful, accurate and fast. However, based on surveys and interviews the author carried out, the information is up to the executive takes a long time. This is partly due to the difficulty that function at the time of data collection, because the source data has not been well organized and still-separated between each other, the recording is still done manually as well as the lack of executive support facilities needs for information. The right solution to solve this problem is to create an Executive Information System application. With the establishment of an Executive Information System Pertamina gas station is intended to help provide information needed by the executive Pertamina to analyze or monitor the development of gas stations in the city of Surabaya is faster and more focused through the report in the form of graphs or tables that can drilldown into a more specific level, so that the information received can be more easily understood and can see detailed information. Keyword : Executive Information System, Gas Station, Pertamina